INVESTIGATING OF LEARNING MOTIVATION ON ENGLISH VOCABULARY MASTERY (A Study at the Seventh Grade Students of Pondok Pesantren Hidayatul Qomariyah) - Meiza Silviana; Risnawati; Andriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research investigates learning motivation factors on the English vocabulary mastery of seventh-grade students at Hidayatul Qomariyah Islamic Boarding School. Vocabulary mastery is critical for effective communication, particularly in learning English as a foreign language. This study explores how both intrinsic and extrinsic motivations influence students’ success in acquiring vocabulary. A qualitative approach was employed, using surveys and interviews to gather data from students and teachers. The findings reveal that intrinsic motivations, such as personal interest in mastering the language, significantly enhance students' engagement and persistence in learning. Extrinsic factors, including teacher support and the classroom environment, also play a vital role in encouraging students to improve their vocabulary. However, challenges such as limited access to digital resources and difficulties with pronunciation and grammar hinder their learning process. The study also found that interactive methods like singing and repetition improve vocabulary retention and motivation. Students who engage with audiovisual media and popular culture, such as English songs, show higher motivation to learn English. This research suggests that schools should provide better access to digital learning tools and create more engaging, interactive teaching methods to boost motivation and vocabulary acquisition. Additionally, a stronger focus on motivation-based teaching strategies may lead to better vocabulary outcomes for students, particularly in rural or less technologically equipped environments. Keywords: learning motivation, vocabulary mastery, intrinsic and extrinsic motivation